Filosofi Manajemen Pendidikan Kekristenan dalam Konteks Sekolah Minggu di Era Disrupsi - Karbui, Titus; Yuli, Purwisasi (Sekolah Tinggi Alkitab Batu, Malang, 2025)
The era of disruption has brought significant changes to the world of education, including in the spiritual education of children within the church environment thru Sunday School. Digitalization, cultural changes, and shifts in family parenting patterns pose serious challenges that require the church to restructure its educational management approach. This article discusses the philosophy of Christian educational management rooted in biblical values and its application in Sunday School ministry amidst the dynamics of the times. Using a theological approach and literature review, this article emphasizes the importance of integrating spiritual values such as love, example, integrity, and service into the entire managerial process, from planning to evaluation. Additionally, strategies such as curriculum revision, teacher training, the use of digital technology, family involvement, and strengthening children's spiritual community are outlined as concrete solutions. It is hoped that this writing will contribute to the church in building relevant, transformative, and faithful Christian educational management amidst the era of disruption.Keywords: Management, Education, Christianity, Sunday School. Abstrak Era disrupsi telah membawa perubahan besar dalam dunia pendidikan, termasuk dalam pendidikan rohani anak di lingkungan gereja melalui Sekolah Minggu. Digitalisasi, perubahan budaya, serta pergeseran pola asuh keluarga menjadi tantangan serius yang mengharuskan gereja untuk menata ulang pendekatan manajemen pendidikannya. Artikel ini membahas filosofi manajemen pendidikan Kristen yang berakar pada nilai-nilai Alkitabiah dan penerapannya dalam pelayanan Sekolah Minggu di tengah dinamika zaman. Dengan menggunakan pendekatan teologis dan kajian literatur, artikel ini menekankan pentingnya integrasi nilai-nilai rohani seperti kasih, keteladanan, integritas, dan pelayanan dalam seluruh proses manajerial,mulai dari perencanaan hingga evaluasi. Selain itu, strategi-strategi seperti revisi kurikulum, pelatihan guru, pemanfaatan teknologi digital, keterlibatan keluarga, dan penguatan komunitas rohani anak diuraikan sebagai solusi konkret. Diharapkan, tulisan ini menjadi kontribusi bagi gereja dalam membangun manajemen pendidikan Kristen yang relevan, transformatif, dan tetap setia pada misi ilahi di tengah era disrupsi. Kata Kunci: Manajemen, Pendidikan Kekristenan, Sekolah Minggu.